2020
DOI: 10.1080/10242694.2020.1799168
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Technological Collaborations and Evolution in the Spanish Defence Industry

Abstract: Collaboration with technological partners as an innovation strategy has become widespread in recent years, and all sectors are immersed in this process. In particular, the defence industry is characterised by the technological complexity of the products and services offered, together with a constant innovation process. However, data that allow us to identify characteristics that are found in collaboration contracts are not usually available in this sector. This could explain the scarcity of research on collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The exploratory phase also included planning and preparing data collection from various sources. Specifically, it involved: (1) an initial contact by a research assistant with respondents (i.e., military personnel, researchers, and experts); (2) the elaboration of interview protocols [44,45] that were based on information previously collected from the literature [16,46,47], reports, and seminars organized by idD-Portugal; and (3) the data collection from the selected sources, which are presented below (Table 1). We selected highly recognized respondents who could describe the phenomenon from different perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…The exploratory phase also included planning and preparing data collection from various sources. Specifically, it involved: (1) an initial contact by a research assistant with respondents (i.e., military personnel, researchers, and experts); (2) the elaboration of interview protocols [44,45] that were based on information previously collected from the literature [16,46,47], reports, and seminars organized by idD-Portugal; and (3) the data collection from the selected sources, which are presented below (Table 1). We selected highly recognized respondents who could describe the phenomenon from different perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…The topics responsible for the growing number of publications since 2018 are mainly related to defence innovation and technology transfer of the Spanish defence industry (Briones-Peñalver et al 2020;Oliva et al 2019;Callado-Muñoz et al 2020), the expansion of the Chinese Defence industry (Béraud-Sudreau and Nouwens 2021; Dominese 2020), and the Brazilian R&D projects (Bernat and Karabag 2018;Silva and Olavo-Quandt 2019;Fernandes et al 2020). The most notable investment in research refers to the Spanish defence industry, which is also shown in Figure 3 (top 3 countries).…”
Section: Findings From the Slrmentioning
confidence: 99%
“…Thus, the work of political scientists and scholars who paid attention to the nature of military conflicts and the search for political solutions to them (Von Clausewitz, 2005;Yamazawa, 1990); scholars who studied the ways and means of rebuilding countries after armed conflicts and full-out war, studied their background, assessed their consequences and the available resources for reconstruction (see, for example, (Barakat & Kapisazovic, 2003;Tzifakis & Tsardanidis, 2006;Lemay-Hébert & Murshed, 2016). There is also potential for development in analyzing conceptual frameworks and practical cases to understand possible tools for post-war reconstruction (Aboushala & Haj Ismail, 2022) or technological cooperation in the defense industry as a factor of sustainable development (Holtström, 2022;Callado-Muñoz et al, 2022;Duginets & Nizheiko, 2022).…”
mentioning
confidence: 99%